Preservation and conservation of historical landmarks: the impact on property development in Kuala Lumpur / Syed Idros Syed Mohsin - Syed Idros, Syed Mohsin (Faculty of Architecture,Planning and Surveying, 1985)
Over the years, much have been written and discussed about the need for preservation of historical buildings<, The controversy is raised every now and then whenever a seemingly historical building is affected one way or another., Arguments both for and against preservation have been raised, quite often, with some justification on both sides. Nevertheless, the need for preservation of genuinely historical buildings, structures and sites are beyond disputeo For a relatively new nation like Malaysia, the need to preserve the physical signs of its history is a crucial element in the attempts of nation building» Whether these structures or sites are pre- or post-independence, modern or ancient, should not be an issue0 One should not adopt a jaundiced view of things, and must be proud of one's history for what they are0 Therefore, one must able to transcend petty political narrow-mindedness in his or hers selection...